Indonesia's Revocation of Political Rights: Criminal Perspectives Philosophy - Efendi, Roni; Zurnetti, Aria; Sukmareni, Sukmareni (Faculty of Law, Andalas University, 2023)
Human rights are fundamental freedoms that are eternally guaranteed to all people as they are the creations of the Almighty God. As a result, it must be protected, supported, and respected. It also must not be disregarded, as neglect and human rights abuses result in human rights violations. Political rights are one of the fundamental rights that must be upheld and safeguarded by the State, the law, and the government. The Criminal Code's provision of criminal penalties for the elimination of political rights in Article 35 (1) (3), where the electoral process and electoral laws are founded, proves to conflict with the State's mission for the preservation and maintenance of political rights. This article's analysis of criminal sanctions that impact citizens' political rights in terms of punishment philosophy is urgently needed.